Job Satisfaction among Employees of Banks: A Comparative Analysis between Public and Private Sector Banks of Punjab, Pakistan - Hussain, Rai Imtiaz (International Journal of Asian Social Science, 2012)
The aim of this study was to examine job satisfaction among private and public banking sector in Punjab Pakistan and how different factors affect the job satisfaction. This research explained the factors which create the job satisfaction. These factors are supervision, job security, promotional opportunities, relationship with co-workers and pay. The result of the study shows that most of the employees in banking sector are satisfied with their job. Positive correlation was found between job satisfaction and job security, good supervision, promotional opportunities, pay and relationship with co-worker. Furthermore, Independent T-test was used to see the job satisfaction between employees of public and private sector. There was no significant difference of satisfaction between Public Sector employees and private sector employee in banking sector.